Improving properties of concrete by fibre reinforced polymers - Govindarajan, S.; Muthuramu, K.L. (Journal of Structural Engineering, 2024)
One of the major drawbacks of plain cement concrete is that it is brittle. The failure will be sudden and catastrophic, particularly in structure, which are subjected to earthquake blast or suddenly applied loads. An ideal solution to overcome the serious disadvantage of plain cement concrete is to add fibers in the concrete to convert it into a ductile material and avoid sudden failure. The present experimental investigation is to study the strength characteristics like compressive strength, split tensile strength, flexural strength of plain cement concrete and glass fibre (1% to 5 %) by volume of content and also mixing of epoxy resin (1% to 5%) by weight of water. In the investigation M50 mix were designed. Many methods have been recommended for mix proportioning of concrete all over the world. ACI method was selected for our project.